Prognostic Power of Pathogen Cell-Free DNA in Staphylococcus aureus Bacteremia. (15th March 2019) - Guimaraes, Alessander O; Gutierrez, Johnny; Maskarinec, Stacey A; Cao, Yi; Hong, Kyu; Ruffin, Felicia; Carrasco-Triguero, Montserrat; Peck, Melicent C; Fowler, Vance G; Baruch, Amos; Rosenberger, Carrie M
Abstract: Background: Staphylococcus aureus is a leading global cause of bacteremia that can cause invasive tissue infections with high morbidity and mortality despite appropriate antibiotic therapy. Clinicians lack sufficient tools to rapidly identify patients with a poor prognosis to guide diagnostic workup and treatment decisions. Host cell-free DNA provides prognostic value across a spectrum of critical illnesses, including S. aureus bacteremia and sepsis. Metrics of high bacterial load are associated with disease severity in S. aureus bacteremia, and the objective of this study was to evaluate whether incorporating quantitation of cell-free bacterial DNA would provide additive prognostic value when combined with biomarkers of the inflammatory response. Methods: S. aureus cell-free DNA was measured by quantitative polymerase chain reaction (PCR) in baseline serum samples from an observational cohort of 111 patients with complicated S. aureus bacteremia and correlated with host inflammatory markers and clinical outcomes. Results: High levels of S. aureus cell-free DNA at the time of positive index blood culture were prognostic for all-cause and attributable mortality and persistent bacteremia and were associated with infective endocarditis. However, they did not provide additive value to biomarkers of the host response to infection in multivariate analysis. Conclusions: Measurements of bacterial load by PCR are a clinically feasible candidate biomarker for stratifying patients at higher risk for complications and poor outcomes. Their diagnostic and prognostic value for identifying foci of infection and influencing treatment remain to be evaluated in additional cohorts.